2016
DOI: 10.1016/j.neuro.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of adolescent exposure to bisphenol A on neuron and glia number in the rat prefrontal cortex: Differences between the sexes and cell type

Abstract: Bisphenol A (BPA), an endocrine disruptor used in a variety of consumer products, has been found to alter the number of neurons in multiple brain areas in rats following exposure in perinatal development. Both the number of neurons and glia also change in the medial prefrontal cortex (mPFC) during adolescence, and this process is known to be influenced by gonadal hormones which could be altered by BPA. In the current study, we examined Long-Evans male and female rats that were administered BPA (0, 4, 40, or 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 40 publications
0
20
1
Order By: Relevance
“…Although there are sex differences in the timing of neuronal loss (Willing and Juraska, 2015) and dendritic complexity (Markham et al, 2013) in adolescence, less is known about sex differences in neuron number in adulthood that could contribute to the changes observed in the PFC. Previous studies have reported no sex differences in the number of neurons in the mPFC in adult Long Evans rats (Koss et al, 2012; Wise et al, 2016). In addition, Sprague Dawley females (P62) exhibit fewer and shorter branches in apical, but not basilar, dendrites in the mPFC, compared to their male counterparts (Garrett and Wellman, 2009).…”
Section: 0 Discussionmentioning
confidence: 74%
“…Although there are sex differences in the timing of neuronal loss (Willing and Juraska, 2015) and dendritic complexity (Markham et al, 2013) in adolescence, less is known about sex differences in neuron number in adulthood that could contribute to the changes observed in the PFC. Previous studies have reported no sex differences in the number of neurons in the mPFC in adult Long Evans rats (Koss et al, 2012; Wise et al, 2016). In addition, Sprague Dawley females (P62) exhibit fewer and shorter branches in apical, but not basilar, dendrites in the mPFC, compared to their male counterparts (Garrett and Wellman, 2009).…”
Section: 0 Discussionmentioning
confidence: 74%
“…Therefore, we do not know whether peripubertal exposure alone would cause the changes observed in the P + P females or whether they may result from a more prolonged exposure to BPA. Peripubertal exposure has been reported to alter microglia number in the prefrontal cortex in female rats [61] and to increase ER alpha levels in several brain nuclei in female but not male mice [62] and rats [63]. As mentioned previously, male and female C57BL/6J mice exposed to BPA solely during the mid through post adolescent period revealed marked increases in body weight and adiposity at the end of the exposure period [50] suggesting that this period could be a critical window for the obesogenic properties of BPA.…”
Section: Discussionmentioning
confidence: 99%
“…Both BPA and phthalates are endocrine disruptors at low levels (Wise et al 2016). Because of their widespread use, exposures are of concern.…”
Section: Endocrine Disruptors Including Bisphenol a Other Bisphenolsmentioning
confidence: 99%
“…BPA has been shown to alter the sex-specific colonization of the hippocampus and amygdala by microglia (Rebuli et al 2016). However, in regard to which gender may be more vulnerable to the neurotoxic effects of BPA, the evidence appears to be somewhat mixed (Wise et al 2016). …”
Section: Bisphenol Amentioning
confidence: 99%